2022
DOI: 10.14256/jce.2301.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects and dynamic behaviour of soil - framed structure interaction

Abstract: The effect and behaviour of soil - framed-structure interaction (SSI) under dynamic load conditions are presented in the paper. All civil engineering structures involve various types of structural elements that are in direct contact with soil. Hence, a new thin-layer interface element, based on the concept of the finite element method, is formulated. The formulation is elaborated using a combination of degrees of freedom of the top and bottom sides of the interface elements. The compatibility conditions of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The design of reinforced concrete columns is an axis of research that has received much attention in recent years. Several experimental [1][2][3][4] and numerical studies on reinforced concrete portal frame elements [5][6][7][8][9][10][11] have been conducted to explore the behaviour of portal frame elements. Alfarah et al [10] presented a new methodology for calculating the evolution of the damage variables on two portal frames.…”
Section: Introductionmentioning
confidence: 99%
“…The design of reinforced concrete columns is an axis of research that has received much attention in recent years. Several experimental [1][2][3][4] and numerical studies on reinforced concrete portal frame elements [5][6][7][8][9][10][11] have been conducted to explore the behaviour of portal frame elements. Alfarah et al [10] presented a new methodology for calculating the evolution of the damage variables on two portal frames.…”
Section: Introductionmentioning
confidence: 99%
“…The different structural configurations, impact models, analyses, and assumptions considered in these studies have indicated that structural pounding amplifies structural responses. Another exaggerating factor is the soil effect, which involves the sliding, rotation, and settlement of foundations during earthquakes [13][14][15][16][17][18][19][20][21]. The assumption of a fixed base that neglects the soil effect is sufficient for structures with low structural rigidity, in which the displacement of the superstructure is more important than that of the foundation.…”
Section: Introductionmentioning
confidence: 99%